Method for co-activating solid waste to produce aluminum, co-producing white carbon black and porous filter material

CN122789403APending Publication Date: 2026-09-22吴彤
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611225795.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-09-22

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种固废协同活化提铝联产白炭黑和多孔滤料的方法,解决了现有粉煤灰提铝工艺中硅铝相分离困难导致氧化铝提取率受限,以及提铝尾渣缺乏消纳途径造成二次固废堆存的问题

Benefits of technology

1、本发明通过超细球磨与恒温焙烧工艺对粉煤灰与电石渣进行预活化,改善了原料的固相反应条件,体系中掺入的氟化钙在高温下破坏了粉煤灰莫来石及玻璃体网络中的硅氧键与铝氧键,降低了反应的表观活化能。游离的硅、铝组分与电石渣提供的氧化钙发生重构,生成反应活性较高的原硅酸二钙和七铝酸十二钙,为后续硅、铝组分的液相提取提供了物相基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122789403A_ABST
    Figure CN122789403A_ABST
Patent Text Reader

Abstract

The present application relates to solid waste resource utilization technical field, disclose a kind of method for solid waste synergic activation extraction of aluminium co-production white carbon black and porous filter material, the method is mixed after fly ash, carbide slag and calcium fluoride is ground by ultrafine ball and constant temperature roasting, obtain activated clinker;Subsequently, activated clinker is placed in sodium hydroxide aqueous solution and leaching, after solid-liquid separation, white carbon black is prepared by passing into carbon dioxide gas and precipitating in sodium silicate enrichment liquid;The first filter cake containing aluminum component is added into sodium carbonate aqueous solution and reflux leaching, and the obtained sodium aluminate enrichment mother liquor is prepared by passing into carbon dioxide and high temperature calcination to obtain aluminum oxide powder;Finally, the net tailings of extracting aluminum are mixed into inorganic-organic composite pore-forming agent and crosslinking modified polymer binder, and porous water treatment filter material is prepared by granulating, forming and high temperature sintering.The present application realizes the step-by-step extraction of silicon and aluminum components by using staged leaching, and the porous filter material is prepared by using tailings, so that the full-component resource utilization of fly ash and carbide slag is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization technology, specifically a method for the co-activation of solid waste to extract aluminum and co-produce precipitated silica and porous filter media. Background Technology

[0002] Fly ash is a major industrial solid waste generated from coal combustion. Due to its high silicon and aluminum content, extracting alumina and silica from it is a common method for realizing the resource utilization of fly ash. However, existing fly ash aluminum extraction processes still face some technical limitations in practical applications.

[0003] During the phase activation and component extraction stages, the stable mullite and glassy structures in fly ash require pretreatment to release their silicon and aluminum components. In conventional alumina extraction processes, during leaching, silicate and aluminate ions simultaneously enter the liquid phase. These two ions react in an alkaline environment, easily generating side reactions and producing insoluble sodium silicate slag precipitate. This precipitate not only consumes the alkaline agent in the leaching system but also causes the target aluminum element in the liquid phase to enter the solid waste, making silicon-aluminum phase separation difficult and reducing the actual extraction rate and purity of alumina.

[0004] After the aluminum extraction process is completed, the entire process generates a large amount of aluminum extraction tailings. These tailings typically consist of calcium compounds, unreacted silicon-aluminum frameworks, and some residual alkaline substances. Their phase structure is relatively stable and lacks conventional hydration activity. Currently, there is a lack of mature and economically viable large-scale disposal methods for this complex secondary solid waste. The long-term accumulation of aluminum extraction tailings not only occupies land but also increases the solid waste disposal costs for enterprises, hindering the large-scale application of fly ash resource utilization technology. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media. This method solves the problems of limited alumina extraction rate due to difficulties in separating the silicon and aluminum phases in existing fly ash aluminum extraction processes, as well as the lack of disposal pathways for aluminum extraction tailings, which leads to secondary solid waste stockpiling.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media includes the following steps: Fly ash and carbide slag are mixed and calcium fluoride is added. The mixture is then ball-milled to obtain a mixed raw meal. The mixed raw materials are subjected to aerobic roasting, and after roasting at the highest constant temperature, they are cooled in the furnace to obtain activated clinker; After the activated clinker is crushed and sieved, it is added to an aqueous sodium hydroxide solution and stirred to leach. The solution is then filtered to obtain a sodium silicate enrichment solution and a primary filter cake. Carbon dioxide gas is introduced into the sodium silicate enrichment solution, and after aging, the solution is filtered, washed, and the precipitate is dried to obtain silica. The primary filter cake was added to a sodium carbonate aqueous solution and refluxed for leaching. Solid-liquid separation was performed to obtain sodium aluminate enriched mother liquor and aluminum-extracting tailings. Carbon dioxide gas was introduced into the mother liquor enriched with sodium aluminate to precipitate the precipitate, which was then filtered, washed, and calcined to obtain alumina powder. The aluminum extraction tailings are dried and ultra-finely ground to pass through a 200-mesh sieve. The dry tailings powder is then mixed with a composite pore-forming agent and a polymer binder. After being sprayed with atomized water, the powder is granulated. The raw material granules are preheated, sintered, kept warm, and cooled in the furnace to obtain porous water treatment filter media.

[0007] By adopting the above technical solution, this invention achieves the synergistic resource utilization of fly ash and carbide slag. This process utilizes a reaction path from premixing to calcination and tiered leaching, enabling the separation of silicon and aluminum components at different reaction stages, while the tailings are recycled into the preparation of filter media. The core of this transformation lies in the destruction and reconstruction of the solid-phase structure.

[0008] During the roasting stage, calcium carbide slag, as a source of calcium oxide, works synergistically with calcium fluoride, which acts as a mineralization medium, to break down the silicon-oxygen and aluminum-oxygen bonds in the original mullite and glassy network of fly ash at high temperatures. This reduces the apparent activation energy of the activation reaction. The released silicate and aluminate anions undergo solid-phase reconstruction with calcium oxide to form highly reactive dicalcium orthosilicate and dodecacalcium heptaaluminate phases.

[0009] After solid-phase reconstruction is completed, this scheme utilizes the difference in solubility characteristics of dicalcium orthosilicate and dodecacalcium heptaaluminate in different leaching media to carry out segmented extraction. Low-concentration sodium hydroxide solution can promote the dissolution of dicalcium orthosilicate to form sodium silicate entering the liquid phase. At this time, dodecacalcium heptaaluminate remains in the solid filter cake due to its stability in a weakly alkaline environment.

[0010] This operation removes the silica-rich liquid phase, avoiding the problem of insoluble sodium silicate slag formed by the coexistence of silicate and aluminate ions during subsequent leaching. For the remaining aluminum-rich filter cake, a sodium carbonate solution is used for leaching. The chemical tendency of carbonate ions to combine with calcium ions to form calcium carbonate precipitate promotes the structural disintegration of dodecacalceheptaaluminate, allowing aluminum to enter the liquid phase as sodium aluminate.

[0011] Preferably, when mixing fly ash and calcium carbide slag, based on a total weight of 100 parts of fly ash and calcium carbide slag, the amount of fly ash is 66.7-80 parts, and the amount of calcium carbide slag is 20-33.3 parts; the amount of calcium fluoride added is 3-8 parts by weight; and the conditions for ultrafine ball milling are as follows: The ball-to-material ratio is controlled at (5-10):1, and the mixture is ultrafinely ball-milled at a speed of 300-500 rpm for 2-4 hours to achieve a characteristic particle size D50 of 5-15 μm for the mixed raw material.

[0012] By adopting the above technical solution and setting the calcium-silicon ratio and calcium-aluminum ratio within this range, the purpose is to ensure that the calcination system has the calcium source required for the phase reconstruction of dicalcium silicate and dodecacalcium heptaaluminate. While reducing the particle size of the material, mechanical ultrafine ball milling will generate certain lattice distortion and mechanical defects on the particle surface, which helps to improve the thermodynamic reaction conditions of the mixed raw materials during the calcination process.

[0013] Preferably, the parameters for the isothermal calcination are controlled as follows: The heating rate is 5-10℃ / min, the calcination constant temperature is set at 850-980℃, and the constant temperature holding time is 1.5-3h.

[0014] By adopting the above technical solution, the temperature and time range corresponds to the phase transition range of the target active mineral phase, which can maintain the normal progress of the activation reaction and prevent the material from sintering, melting and agglomerating, or forming an insoluble calcium feldspar phase due to excessive temperature, thus maintaining the stability of the leaching process.

[0015] Preferably, the specific conditions for pulverizing and sieving the activated clinker are: pulverizing and sieving through a 100-mesh standard sieve; The sodium hydroxide aqueous solution has a mass fraction of 5-10%, and the liquid-to-solid ratio of the activated clinker to the sodium hydroxide aqueous solution is (4-8):1mL / g; Under a water bath at 60–90°C, mechanical stirring at a speed of 200–400 rpm is turned on, and the leaching time is controlled at 30–60 min. Carbon dioxide gas is introduced into the sodium silicate enrichment solution, and the pH value at the reaction endpoint is controlled at 7.5–8.5. The solution is then left to stand and age at room temperature for 1–2 h.

[0016] By adopting the above technical solution, the use of a lower concentration of alkaline solution in combination with a medium-low temperature water bath can improve the selectivity of calcium silicate phase extraction. The liquid-solid ratio and stirring speed provide mass transfer driving force for the diffusion of free silicate ions into the liquid phase, while the control of the pH value at the reaction endpoint helps silicate ions to be converted into metasilicic acid precipitate, thereby ensuring the yield of silica products.

[0017] Preferably, the specific conditions for reflux leaching in the sodium carbonate aqueous solution are as follows: The sodium carbonate aqueous solution has a mass fraction of 15-25%, and the liquid-solid ratio of the primary filter cake to the sodium carbonate aqueous solution is (3-6):1mL / g. Stir and reflux at 80–110°C for 1.5–3 hours; The calcination temperature after precipitation is controlled at 1000-1100℃, and the calcination time is 2h.

[0018] By adopting the above technical solution, carbonate ions promote the ion replacement process at the above reflux temperature, destroying the lattice of calcium heptacalcium aluminate, so that more aluminate ions are transferred to the enriched mother liquor, and the calcium carbonate generated by the reaction is retained in the aluminum-removing tailings, forming the internal skeleton of the subsequent porous filter media.

[0019] This invention provides a porous filter material forming formula and sintering mechanism, employing the following technical solution: The composite pore-forming agent is an inorganic-organic composite pore-forming agent, and the polymer binder is a cross-linked modified sodium alginate-polyacrylamide binder; When incorporating the inorganic-organic composite pore-forming agent and the cross-linked modified sodium alginate-polyacrylamide binder, based on 100 parts by weight of the dry powder of aluminum-removing tailings, the amount of the inorganic-organic composite pore-forming agent added is 2-5 parts by weight, the amount of the cross-linked modified sodium alginate-polyacrylamide binder added is 1-3 parts by weight, and the amount of atomized water sprayed is 10-20 parts by weight.

[0020] The specific conditions for granulation and sintering are as follows: Spherical raw material pellets with a particle size of 3mm to 8mm are prepared by molding in a disc pelletizer at an inclination angle of 45° to 55° and a rotation speed of 15 to 30 rpm. The raw material particles are first preheated at 400-500℃ and kept at that temperature for 30-60 minutes, then heated to 1050-1180℃ for high-temperature microporous sintering and held at that temperature for 1-2 hours.

[0021] The inorganic-organic composite pore-forming agent is made from raw material components comprising the following weight ratios: 100 parts ammonium bicarbonate and 100-200 parts corn starch. The above raw materials are placed in a three-dimensional mixer and mechanically dry-mixed at room temperature and a speed of 30 r / min for 45 min. After being mixed evenly, the mixture is passed through a 100-mesh standard sieve.

[0022] By adopting the above technical solution, a combined pore-forming process is established in the formulation system. When the raw material particles are in the preheating stage, ammonium bicarbonate undergoes thermal decomposition and releases ammonia and carbon dioxide, generating a microporous network inside the pellet.

[0023] As the temperature rises further into the high-temperature sintering range, corn starch undergoes oxidation and combustion, creating interconnected channels, while calcium carbonate in the aluminum extraction tailings partially decomposes to expand the macroporous structure. The synergistic effect of different pore-forming mechanisms within their respective temperature ranges results in water treatment filter media possessing a certain porosity and water flow permeability.

[0024] This invention provides a method for preparing an environmentally friendly adhesive, employing the following technical solution: An environmentally friendly adhesive is made from raw materials comprising 100 parts by weight of deionized water, 2-5 parts by weight of sodium alginate, 10-15 parts by weight of acrylamide, 0.1-0.3 parts by weight of potassium persulfate, and 0.05-0.15 parts by weight of N,N'-methylenebisacrylamide.

[0025] The cross-linked modified sodium alginate-polyacrylamide environmentally friendly binder is prepared through the following specific steps: Sodium alginate was dissolved in deionized water and heated in a water bath to 60-70°C under nitrogen protection, with continuous mechanical stirring until completely dissolved. Acrylamide, potassium persulfate, and N,N'-methylenebisacrylamide were then added sequentially. The mixture was continuously stirred mechanically at a constant temperature of 60–70°C for 3–5 hours to form a viscous graft copolymer gel. After the reaction was completed, the product was washed with anhydrous ethanol to remove the precipitate. After being pulverized, the product was dried in a vacuum drying oven at 60°C for 24 hours to obtain a solid binder powder.

[0026] By adopting the above technical solution, the cross-linked polymer synthesized by this method has a three-dimensional interpenetrating network structure. Potassium persulfate in the system acts as an initiator to promote the graft copolymerization of acrylamide monomers on the sodium alginate backbone, and cross-links and solidifies the polymer segments with N,N'-methylenebisacrylamide.

[0027] This binder exhibits viscoelastic characteristics after dissolving in water. It uses its macromolecular chains to wrap and entangle the aluminum-removing tailings particles that lack molding activity, increasing the compressive strength of the raw material particles in both wet and dry states. This reduces the pulverization and collapse of the filter media blanks during the preheating and adhesive removal process.

[0028] This invention provides a method for the co-activation of solid waste to extract aluminum and co-produce silica and porous filter media. It has the following beneficial effects: 1. This invention pre-activates fly ash and carbide slag through ultrafine ball milling and isothermal calcination, improving the solid-phase reaction conditions of the raw materials. The calcium fluoride incorporated into the system disrupts the silicon-oxygen and aluminum-oxygen bonds in the mullite and glassy network of the fly ash at high temperatures, reducing the apparent activation energy of the reaction. The free silicon and aluminum components undergo remodeling with the calcium oxide provided by the carbide slag, generating highly reactive dicalcium orthosilicate and dodecacalcium heptaaluminate, providing a physical basis for the subsequent liquid-phase extraction of the silicon and aluminum components.

[0029] 2. This invention employs differentiated leaching media to achieve segmented extraction of silicon and aluminum components. Initial leaching of activated clinker is performed using a sodium hydroxide aqueous solution, causing dicalcium silicate to preferentially dissolve and form sodium silicate in the liquid phase. At this point, dodecacalcium heptaaluminate remains stable and is retained in the filter cake. For the aluminum-rich filter cake, a sodium carbonate aqueous solution is used for reflux leaching. The tendency of carbonate ions to combine with calcium ions promotes the disintegration of the dodecacalcium heptaaluminate structure and releases sodium aluminate. This stepwise operation avoids the reaction path of silicate and aluminate coexisting to form insoluble sodium silicate slag, thus improving the silicon-aluminum separation effect.

[0030] 3. This invention transforms alumina extraction tailings into porous water treatment filter media, solving the problem of large-scale secondary solid waste accumulation in conventional alumina extraction processes. The formula introduces cross-linked modified sodium alginate-polyacrylamide binder, which, through the entanglement and encapsulation of tailings particles by its macromolecular chain segments, improves the wet and dry compressive strength of raw material particles, preventing pulverization and detachment in the early stage of sintering. Combined with the thermal decomposition and oxidation reaction of inorganic-organic composite pore-forming agent in different temperature ranges during preheating and sintering, a multi-scale pore network is constructed inside the particle body, ultimately realizing a closed-loop resource utilization of all components of fly ash and carbide slag. Attached Figure Description

[0031] Figure 1 This is a distribution chart of the segmented extraction rate and product purity data of the present invention; Figure 2 This is a macroscopic physicochemical and environmental safety distribution diagram of the porous water treatment filter media of the present invention; Figure 3 This diagram illustrates the quantitative impact of the core process features of this invention on the efficiency of the silicon / aluminum extraction system. Figure 4 The above is a comparative test distribution diagram of the water treatment functional indicators of the filter media of the present invention. Among them, (a) is a distribution line spectrum of dynamic filtration pressure drop and methylene blue adsorption value of each test bed, and (b) is a distribution line spectrum of dynamic breakthrough time and saturated adsorption capacity of copper ions under heavy metal simulated wastewater test. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Preparation Example 1: This preparation example provides a method for preparing a cross-linked modified sodium alginate-polyacrylamide environmentally friendly adhesive, including the following steps: Dissolve 2g of sodium alginate in 100mL of deionized water, heat in a water bath to 60℃ under nitrogen protection, and stir mechanically until completely dissolved. Then, 10g of acrylamide, 0.1g of potassium persulfate, and 0.05g of N,N'-methylenebisacrylamide were added sequentially. The reaction was carried out under constant temperature of 60℃ with continuous mechanical stirring for 3 hours to form a viscous graft copolymer gel. After the reaction was completed, the product was washed in anhydrous ethanol to remove the precipitate. After being pulverized, it was dried in a vacuum drying oven at 60°C for 24 hours to obtain a solid environmentally friendly binder powder.

[0034] Preparation Example 2: This preparation example provides a method for preparing a cross-linked modified sodium alginate-polyacrylamide environmentally friendly adhesive, including the following steps: Dissolve 3.5g of sodium alginate in 100mL of deionized water, heat in a water bath to 65℃ under nitrogen protection, and stir mechanically continuously until completely dissolved; Then, 12.5g of acrylamide, 0.2g of potassium persulfate, and 0.1g of N,N'-methylenebisacrylamide were added sequentially. The reaction was carried out under constant temperature of 65℃ with continuous mechanical stirring for 4 hours to form a viscous graft copolymer gel. After the reaction was completed, the product was washed in anhydrous ethanol to remove the precipitate. After being pulverized, it was dried in a vacuum drying oven at 60°C for 24 hours to obtain a solid environmentally friendly binder powder.

[0035] Preparation Example 3: This preparation example provides a method for preparing a cross-linked modified sodium alginate-polyacrylamide environmentally friendly adhesive, including the following steps: Dissolve 5g of sodium alginate in 100mL of deionized water, heat in a water bath to 70℃ under nitrogen protection, and stir continuously with mechanical stirring until completely dissolved; Then, 15g of acrylamide, 0.3g of potassium persulfate, and 0.15g of N,N'-methylenebisacrylamide were added sequentially. The reaction was carried out under constant temperature of 70℃ with continuous mechanical stirring for 5 hours to form a viscous graft copolymer gel. After the reaction was completed, the product was washed in anhydrous ethanol to remove the precipitate. After being pulverized, it was dried in a vacuum drying oven at 60°C for 24 hours to obtain a solid environmentally friendly binder powder.

[0036] Preparation Example 4: This preparation example provides a method for preparing an inorganic-organic composite pore-forming agent, including the following steps: Accurately weigh 100g of ammonium bicarbonate and 100g of corn starch, place them in a three-dimensional mixer, and mechanically dry mix them at room temperature and a speed of 30r / min for 45min. After mixing evenly, pass the mixture through a 100-mesh standard sieve and collect the sieve material to obtain the inorganic-organic composite pore-forming agent.

[0037] Preparation Example 5: This preparation example provides a method for preparing an inorganic-organic composite pore-forming agent, including the following steps: Accurately weigh 100g of ammonium bicarbonate and 150g of corn starch, place them in a three-dimensional mixer, and mechanically dry mix them at room temperature and a speed of 30r / min for 45min. After mixing evenly, pass the mixture through a 100-mesh standard sieve and collect the sieve material to obtain the inorganic-organic composite pore-forming agent.

[0038] Preparation Example 6: This preparation example provides a method for preparing an inorganic-organic composite pore-forming agent, including the following steps: Accurately weigh 100g of ammonium bicarbonate and 200g of corn starch, place them in a three-dimensional mixer, and mechanically dry mix them at room temperature and a speed of 30r / min for 45min. After mixing evenly, pass the mixture through a 100-mesh standard sieve and collect the sieve material to obtain the inorganic-organic composite pore-forming agent. Example 1

[0039] This embodiment provides a method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media, including the following steps: Raw material premixing and mechanical preactivation: Weigh 75 kg of fly ash and 25 kg of carbide slag (mass ratio of 3:1), and add 5.5 kg of calcium fluoride. Place the mixture in a planetary ball mill, control the ball-to-material ratio at 7.5:1, and ball mill at 400 rpm for 3 hours to achieve a characteristic particle size D50 of 10 μm for the mixed raw material.

[0040] Multi-stage low-temperature co-firing activation: The pre-activated raw material is fed into a rotary kiln for aerobic roasting, with the heating rate controlled at 7.5℃ / min, the maximum constant temperature set at 920℃, and the constant temperature holding time at 2 hours. After roasting, the material is cooled with the furnace to obtain activated clinker.

[0041] Segmented step-by-step leaching and product extraction: Desilication stage: The activated clinker was pulverized and passed through a 100-mesh sieve. A 7.5% sodium hydroxide aqueous solution was prepared, and the clinker was added to the alkaline solution at a liquid-to-solid ratio of 6:1 (mL / g). The mixture was then leached for 45 minutes at 300 rpm in a 75°C water bath. After the reaction was completed, the mixture was filtered to obtain a sodium silicate enrichment solution and a primary filter cake. Carbon dioxide gas was introduced into the sodium silicate enrichment solution to control the final pH value at 8.0. After standing and aging for 1.5 hours, the mixture was filtered and washed. The precipitate was dried at 110°C to obtain silica.

[0042] Aluminum extraction stage: Prepare a 20% sodium carbonate aqueous solution. Add the primary filter cake to the solution at a liquid-to-solid ratio of 4.5:1 (mL / g). Leach under stirring and reflux at 95℃ for 2 hours. After the reaction, separate the solid and liquid phases to obtain sodium aluminate enriched mother liquor and aluminum-extracting tailings. Pass carbon dioxide gas into the mother liquor to precipitate the precipitate. After filtration and washing, calcine at 1050℃ for 2 hours to obtain alumina powder.

[0043] Closed-loop preparation of porous water treatment filter media from tailings: Aluminum extraction tailings were dried at 105℃ and ultrafine ground to pass through a 200-mesh sieve. 100 kg of the dry tailings powder was taken and uniformly mixed with 3.5 kg of the composite pore-forming agent obtained in Preparation Example 5 and 2.0 kg of the environmentally friendly binder obtained in Preparation Example 2. 15 kg of atomized water was sprayed on the mixture, and it was shaped in a disc granulator at an inclination angle of 50° and a rotation speed of 20 rpm to prepare spherical raw material particles with a particle size of 3 mm-8 mm. The raw material particles were fed into a kiln and preheated at 450℃ for 45 min, then heated to 1100℃ for high-temperature microporous sintering and held at that temperature for 1.5 h. After cooling in the furnace, high-strength porous water treatment filter media was obtained. The leaching and washing wastewater was collected, conditioned, and reused in the process flow. Example 2

[0044] This embodiment provides a method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media, including the following steps: Raw material premixing and mechanical preactivation: Weigh 66.7 kg of fly ash and 33.3 kg of carbide slag (mass ratio of the two is 2:1), add 3 kg of calcium fluoride, control the ball-to-material ratio to be 5:1, and ball mill at 300 rpm for 2 hours to make the characteristic particle size D50 of the mixed raw material reach 15 μm.

[0045] Multi-stage low-temperature synergistic roasting activation: The heating rate is controlled at 5℃ / min, the roasting constant temperature is set at 850℃, and the constant temperature holding time is 1.5h to obtain activated clinker.

[0046] Segmented step-by-step leaching and product extraction: Desilication stage: After clinker is crushed and sieved, it is added to a 5% sodium hydroxide aqueous solution at a liquid-to-solid ratio of 4:1 (mL / g). The mixture is stirred and leached for 30 minutes in a 60℃ water bath at 200 rpm. The resulting sodium silicate enrichment and primary filter cake are obtained by filtration. Carbon dioxide is bubbled through the solution until the pH reaches 7.5. After aging for 1 hour, the solution is washed and dried at 105℃ to obtain silica.

[0047] Aluminum extraction stage: The primary filter cake was added to a 15% sodium carbonate aqueous solution at a liquid-to-solid ratio of 3:1 (mL / g), and leached under reflux at 80℃ for 1.5 h. Solid-liquid separation yielded sodium aluminate enriched mother liquor and aluminum extraction tailings. Carbon dioxide was passed through the mother liquor to precipitate the precipitate, which was then calcined at 1000℃ for 2 h to obtain alumina powder.

[0048] Closed-loop preparation of porous water treatment filter media from tailings: 100 kg of tailings powder was mixed with 2 kg of the composite pore-forming agent obtained in Preparation Example 4 and 1 kg of the environmentally friendly binder obtained in Preparation Example 1. 10 kg of atomized water was sprayed, and the mixture was shaped in a disc granulator at an inclination angle of 45° and a rotation speed of 15 rpm. The raw material granules were preheated at 400°C for 30 min, then sintered at 1050°C for 1 h, and cooled to obtain the porous water treatment filter media. The remaining wastewater was treated in the same manner as in Example 1. Example 3

[0049] This embodiment provides a method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media, including the following steps: Raw material premixing and mechanical preactivation: Weigh 80 kg of fly ash and 20 kg of carbide slag (mass ratio of 4:1), and add 8 kg of calcium fluoride. Control the ball-to-material ratio at 10:1, and ball mill at 500 rpm for 4 hours to achieve a characteristic particle size D50 of 5 μm for the mixed raw materials.

[0050] Multi-stage low-temperature synergistic roasting activation: The heating rate is controlled at 10℃ / min, the roasting constant temperature is set at 980℃, and the constant temperature holding time is 3h to obtain activated clinker.

[0051] Segmented step-by-step leaching and product extraction: Desilication stage: After clinker is crushed and sieved, it is added to a 10% sodium hydroxide aqueous solution at a liquid-to-solid ratio of 8:1 (mL / g). The mixture is stirred and leached for 60 min at 90℃ and 400 rpm in a water bath. The resulting sodium silicate enrichment and primary filter cake are obtained by filtration. Carbon dioxide is bubbled through the filter until the pH reaches 8.5. After aging for 2 h, the mixture is washed and dried at 120℃ to obtain silica.

[0052] Aluminum extraction stage: The primary filter cake was added to a 25% sodium carbonate aqueous solution at a liquid-to-solid ratio of 6:1 (mL / g), and refluxed at 110℃ for 3 hours. Solid-liquid separation yielded sodium aluminate enriched mother liquor and aluminum extraction tailings. Carbon dioxide was passed through the mother liquor to precipitate the precipitate, which was then calcined at 1100℃ for 2 hours to obtain alumina powder.

[0053] Closed-loop preparation of porous water treatment filter media from tailings: 100 kg of tailings powder was mixed with 5 kg of the composite pore-forming agent obtained in Preparation Example 6 and 3 kg of the environmentally friendly binder obtained in Preparation Example 3. 20 kg of atomized water was sprayed, and the mixture was shaped in a disc granulator at an inclination angle of 55° and a rotation speed of 30 rpm. The raw material granules were preheated at 500°C for 60 min, then sintered at 1180°C for 2 h, and cooled to obtain the porous water treatment filter media. The remaining wastewater was treated in the same manner as in Example 1. Example 4

[0054] This embodiment provides a method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media, including the following steps: The first step of raw material pre-activation and the second step of roasting activation in this embodiment are exactly the same as those in Example 1. In the third step of segmented leaching, the desilication stage is adjusted as follows: The clinker was added to a 10% sodium hydroxide aqueous solution at a liquid-to-solid ratio of 6:1 (mL / g), and stirred and leached in a 90°C water bath for 60 min (using the upper limit of the concentration, temperature and time). The remaining steps for preparing silica were the same as in Example 1. The operation steps and parameters for the aluminum extraction stage were exactly the same as in Example 1. The operation steps and parameters for preparing porous water treatment filter media from tailings in the fourth step are exactly the same as in Example 1. Example 5

[0055] This embodiment provides a method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media, including the following steps: The operation steps and parameters of the first step of raw material pre-activation, the second step of roasting activation, and the third step of segmented leaching and extraction in this embodiment are exactly the same as those in Example 1. In the fourth step of preparing porous water treatment filter media by closed-loop preparation of tailings, the following adjustment is made: take 100 kg of dry powder of the tailings and evenly mix it with 5 kg of the composite pore-forming agent obtained in Preparation Example 4 and 1.5 kg of the environmentally friendly binder obtained in Preparation Example 1.

[0056] Spray 15kg of atomized water and form it in a disc granulator at an inclination angle of 50° and a rotation speed of 20rpm. Then, send the raw material granules into a kiln and preheat them at 450℃ for 45 minutes. After that, raise the temperature to 1080℃ for high-temperature microporous sintering and hold for 1.5 hours. After cooling, you will get porous water treatment filter media.

[0057] Comparative Example 1: Compared with Example 1, the difference is that mechanical ultrafine ball milling pre-activation was not performed in the first step. Instead, fly ash, carbide slag and calcium fluoride were simply mixed in a conventional mixer. The rest were the same.

[0058] Comparative Example 2: Compared with Example 1, the difference is that calcium fluoride was not added to the raw materials in the first step, and only fly ash and carbide slag were ball-milled and roasted, while the rest were the same.

[0059] Comparative Example 3: Compared with Example 1, the difference is that the third step did not involve kinetic-controlled segmented leaching. Instead, the activated clinker was directly added to a mixed strong alkaline solution of sodium hydroxide and sodium carbonate and leached at 95°C at a high temperature. All other steps were the same.

[0060] Comparative Example 4: Compared with Example 1, the difference is that the aluminum-removing tailings produced by this process were not used in the fourth step. Instead, an equal amount of raw fly ash powder was directly taken, and pore-forming agent and binder were added in the same proportion for granulation and sintering. The rest were the same.

[0061] Test Example 1: Test objective: This test aims to verify the effect of solid waste co-activation and the practical feasibility of silicon-aluminum kinetic separation in a staged leaching process. The test subjects are the intermediate mother liquor and final refined powder products generated in the leaching section of Examples 1 to 5 and Comparative Examples 1 to 3.

[0062] Test steps: The leaching solutions from each embodiment and comparative example after the first stage of desilication reaction were collected. A fixed volume of liquid sample was accurately measured, and the concentrations of silicon and aluminum in the solution were determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). Based on the total mass of silicon and aluminum in the initial fly ash in the material balance system, the primary desilication rate and aluminum loss rate were calculated in reverse.

[0063] The sodium aluminate mother liquor after the second aluminum extraction reaction was collected, and the total aluminum content in the filtrate was determined by plasma atomic emission spectrometry. Combined with the aluminum loss data in the desilication stage, the final comprehensive alumina extraction rate was calculated.

[0064] After the first stage of carbon precipitation, the silica powder was washed and dried. A fixed mass sample was weighed and placed in a platinum crucible. The mass fraction of silica in the powder was accurately determined by the hydrofluoric acid-sulfuric acid gravimetric method, and the purity of the silica product was determined accordingly.

[0065] The alumina powder after the second carbon fraction was collected and calcined at high temperature was subjected to full elemental quantitative analysis using X-ray fluorescence spectrometry to determine the mass fraction of the main phase aluminum oxide and thus the final purity of the alumina.

[0066] Test data: Table 1. Results of leaching extraction rate and product purity tests in the examples and comparative examples

[0067] Note: In Comparative Example 3, " / " indicates that this data was not measured. Because Comparative Example 3 uses simultaneous strong alkali leaching and does not have a separate desilication stage, the aluminum loss rate of its desilication liquid is not applicable. The final extraction rate of the mixed extraction system is measured directly.

[0068] in conclusion: The test data in Table 1 and Figure 1 The line graph showing the overall data distribution reflects the reaction state under different parameter systems. Figure 1 The four broken lines, characterized by different grayscale line types, respectively show the percentage evolution trends of the primary desilication rate, alumina extraction rate, and purity of silica and alumina products for each test sample. The horizontal axis corresponds from left to right to Examples 1 to 5 and Comparative Examples 1 to 3, which serve as benchmark references.

[0069] Figure 1 The data from Examples 1 to 5 were relatively concentrated and stable. Each example maintained stable reaction efficiency within the set parameter fluctuation range, with alumina extraction rate remaining above 83% and product purity meeting conventional industrial application standards. This stable data output verifies the process robustness of the calcium fluoride and carbide slag composite mineralization system in the medium-temperature range of 850℃-980℃.

[0070] In Example 4, after adjusting the temperature and time of the desilication reaction to the boundary conditions, the single-stage desilication rate increased, but the aluminum loss rate in the desilication solution also increased to 3.12%, ultimately leading to a decrease in the overall alumina extraction rate. This slight decrease in value is very consistent with the kinetic evolution of phase dissolution in multiphase systems, indicating that mild leaching conditions can indeed act as a chemical barrier to inhibit the premature entry of the aluminum phase into the liquid phase.

[0071] Figure 1 In the comparative region of the latter part of the horizontal axis, the broken lines of each index showed a decrease, reflecting the process defects when the composite mechanism of the present invention was not adopted. Comparative Example 1 removed the mechanical ultrafine ball milling process. In the study of powder physicochemical properties, if the mullite lattice and dense glass of fly ash fail to generate structural defects sufficient to reduce the activation energy through high-energy collisions, the severe reduction of the reaction interface will directly hinder the subsequent silicon-aluminum conversion under the same calcination conditions, resulting in a decrease in the extraction rate and purity values ​​in the chart.

[0072] The test results of Comparative Example 2 show that the phase reconstruction of the system is hindered due to the lack of polarization effect of calcium fluoride, and the silicon-oxygen bridge bond cannot be broken by calcium hydroxide alone at 920℃. Its aluminum extraction rate is only 34.05%, indicating that fluoride ions play a key mineralization role in the low-temperature eutectic reaction.

[0073] When activated clinker is directly placed in a high-temperature strong alkali for simultaneous leaching, the alumina extraction rate drops sharply to 42.14%. The dicalcium orthosilicate and dodecacalcium heptaaluminate generated in the activated clinker co-dissolve instantly in the strong alkaline liquid phase. A large number of free silicate and aluminate ions rapidly capture sodium ions in the solution under thermodynamic drive, thereby precipitating the extremely insoluble hydrated sodium aluminosilicate sodalite phase.

[0074] This associated reaction re-solidifies the released silicon and aluminum elements into sodium silicon slag, hindering the extraction of the target product and increasing alkali consumption. The system described in the aforementioned examples avoids this predicament.

[0075] By leveraging the difference in dissolution rates between the dicalcium orthosilicate and aluminum phases under a specific temperature field, the process scheme sets strict time and concentration thresholds, enabling the extraction of the silica-rich mother liquor before the aluminum phase undergoes large-scale dissolution. This time-based separation blocks the synthesis pathway of sodium silicate slag, thus supporting... Figure 1 The data on the high-ranking alumina precipitation and purification on the left are for independent precipitation and purification.

[0076] Test Example 2: Test objective: This test aims to evaluate the engineering properties, adsorption efficiency, and solidification of toxic elements in porous water treatment filter media prepared using alumina extraction tailings. The test subjects were the molded porous filter media prepared under various parameter combinations in Examples 1 to 5, and the reference filter media prepared in Comparative Example 4 using undisturbed fly ash and the same sintering process.

[0077] Test steps: After sintering and cooling, filter media particles from each batch were extracted, and the apparent density and macroscopic porosity of the particles were determined using the Archimedes displacement method combined with vacuum saturated water operation. For each test, 20 filter media particles of uniform size were randomly selected for measurement, and the arithmetic mean was taken after removing extreme values ​​as the basic index of the batch of samples.

[0078] The filter media to be tested was placed under a universal testing machine, and the loading rate was set to 2 mm / min. The critical failure load at which a single particle of filter media ruptured was recorded. The compressive strength of a single particle was calculated based on the average cross-sectional area of ​​the particles to evaluate the mechanical bearing limit of the sintered skeleton in the bottom environment of a water treatment filter.

[0079] Accurately prepare lead ions (Pb) with an initial mass concentration of 50 mg / L. 2+ Simulated wastewater was used. The sample was added at a solid-liquid ratio of 2g of filter media per liter, and the mixture was continuously shaken in a constant-temperature shaker for 24 hours. The supernatant was filtered through a microporous membrane, and the residual lead ion concentration was determined using an atomic absorption spectrophotometer. The saturated adsorption capacity of heavy metals per unit mass of filter media was calculated.

[0080] According to the national standard procedure for leaching toxicity of solid waste, the pulverized filter material was mixed with deionized water at a liquid-to-solid ratio of 1:10 and continuously extracted by turning the mixture in a rotary shaker for 18 hours. The leachate was collected, and the concentration of free fluoride ions in the solution was determined by ion chromatography to determine whether the fluorine element introduced by the fluxing process in the early stage was solidified into the crystal lattice during the high-temperature sintering stage.

[0081] Test data: Table 2. Macroscopic physicochemical and environmental safety test results of porous water treatment filter media in the examples and comparative examples.

[0082] in conclusion: Figure 2 This is a comprehensive distribution diagram of the macroscopic physicochemical and environmental safety test results of porous water treatment filter media in the embodiments and comparative examples of the present invention. The diagram uses a dual vertical axis system to present the evolution trend of the four core indicators. The left vertical axis corresponds to the macroscopic porosity and heavy metal lead ion adsorption data, and the right vertical axis corresponds to the single particle compressive strength and fluoride ion leaching concentration data. The horizontal axis objects in the diagram correspond to Examples 1 to 5 and the original fly ash-based comparative example 4 used for comparison.

[0083] Figure 2 The high-level data range on the left shows that the porous filter media prepared in Examples 1 to 5 maintained a stable porosity between 58% and 69%, and the corresponding apparent density was generally lower than that of water, exhibiting typical characteristics of a lightweight and highly porous structure. Combined with the deduction of the reaction network evolution mechanism, the large amount of ultrafine calcium carbonate enriched in the tailings of the aluminum extraction section became the core excitation source for subsequent pore formation.

[0084] When these precursors undergo thermal decomposition in the high-temperature sintering zone at 1050℃-1180℃, the released carbon dioxide gas escapes within the aluminosilicate preform, generating an in-situ foaming effect. This interconnected three-dimensional porous network widens the fluid penetration channels and increases the exposed area of ​​the active interface, enabling each embodiment to achieve a unit adsorption capacity of over 20 mg / g for heavy metal lead ions.

[0085] The hydrometallurgical process alters the chemical composition of the tailings. After the system is porous, the surface of the framework exposes hydroxyl active sites formed by the hydration of calcium oxide, providing a material basis for the chemical coordination adsorption of heavy metals in the aqueous phase. Cyclic leaching experiments show that this in-situ pore-forming process based on tailings not only changes the material morphology but also endows it with chemical adsorption properties.

[0086] observe Figure 2The evolution trend corresponding to the right coordinate axis shows that the compressive strength of the single particle of the filter media in the example is stably distributed between 3.85MPa and 5.11MPa. The particles did not show pulverization or loosening under mechanical loading, and are fully capable of coping with the pressure load at the bottom of the conventional dynamic water treatment bed and the wear of backwash fluid.

[0087] The residual fluoride ions in the system act as a low-melting-point network modifier during the sintering phase transformation stage, promoting the liquid-phase sintering reaction between the active calcium oxide and calcium silicate phases, forming a continuous phase support framework dominated by tricalcium silicate.

[0088] The fluoride ion leaching concentration in all embodiments remained below 0.5 mg / L, which is lower than the emission limit of the national environmental protection standard. This indicates that the previously introduced fluorine element has been encapsulated and solidified inside the crystal lattice, blocking the leaching migration path of the element.

[0089] In Comparative Example 4, where undisturbed fly ash was directly sintered, the porosity decreased to 23.6%, and the apparent density increased to 1.45 g / cm³. 3 The corresponding lead ion adsorption capacity decreased to 4.1 mg / g. Fly ash that has not undergone alkali dissociation lacks a carbon source carrier, and relying solely on external pore-forming agents cannot form a continuous porous network within a dense substrate. Although its compressive strength reaches 7.84 MPa, the pore space and active adsorption interface are reduced.

[0090] Data comparison shows that when using tailings to prepare derivative materials, changing the internal phase structure through pre-processing chemical processes is a key step in improving the final material's engineering performance.

[0091] Test Example 3: Test objective: This test aims to quantify and verify the absolute weight of the three core process features—mechanical-chemical pre-activation, intermediate-temperature calcium fluoride mineralization, and kinetic staged leaching—in the entire solid waste extraction system from the perspective of reverse stripping. The test subjects are the intermediate clinker produced in the roasting section of Example 1 (complete process baseline) and Comparative Examples 1, 2, and 3, as well as the refined powder finally recovered in the leaching section.

[0092] Test steps: Intermediate clinker samples from each batch, co-roasted between 850℃ and 980℃ and then naturally cooled, were collected. A fixed mass of powder was placed in a reaction vessel, and a forced total dissolution test was performed on the clinker using sodium carbonate solution combined with the standard carbonation decomposition method. The dissolution liquid was collected, and the total amount of silicon and aluminum in the liquid phase was determined. The actual percentage of inert silicon and aluminum components in the raw coal ash during the roasting stage converted into active dicalcium orthosilicate and dodecacalcium heptaaluminate was calculated in reverse.

[0093] The leaching, refining, and carbon precipitation processes for each group were fully executed, and the final dried and calcined silica and alumina products were collected. The net weight of the powder was accurately weighed using a large-scale industrial balance, and the absolute powder recovery rate was calculated per 100 kg of initial dry ash mixture.

[0094] The filtration residues from each stage of the desilication and aluminization process were extracted, washed and dried multiple times with deionized water, and then digested and destroyed using a microwave digester in conjunction with a mixed acid system. The loss of locked free or secondary bound silicon and aluminum elements in the solid residues was tracked by inductively coupled plasma mass spectrometry to verify the accuracy of the closed-loop data of the material balance of the entire system.

[0095] Test data: Table 3. Results of Silicon / Aluminum Extraction Efficiency Tests for Missing Process Features in Examples and Comparative Examples

[0096] Note: The absolute recovery yields in the table refer to the net mass of the target powder produced per 100 kg (total dry weight of fly ash and carbide slag) of initial mixed raw materials consumed.

[0097] in conclusion: Figure 3 This is a quantitative comparative line graph showing the impact of the core process features of this invention on the efficiency of the silicon / aluminum extraction system. The graph is based on a pure grayscale design and uses a dual vertical coordinate system. The solid black line and dashed line on the left correspond to the evolution of the percentage of active conversion of the silicon-aluminum phase inside the roasted clinker. The discontinuous lines of different grayscale on the right represent the absolute recovery yield (kg) of silica and alumina per unit of ash. The objects on the horizontal axis in the graph correspond to the benchmark optimal Example 1 and Comparative Examples 1, 2, and 3, which are missing different process steps, respectively.

[0098] Example 1 demonstrated a high conversion level in the thermodynamic reconstruction and kinetic separation stages, with an active silicon conversion rate of 87.41% and an absolute alumina recovery of 31.05 kg, verifying the feasibility of the proposed process system.

[0099] For Comparative Example 1, which did not undergo mechanical ultrafine ball milling pretreatment, the conversion rate of the active phase in the clinker dropped to about 60%. The highly polymerized mullite crystalline phase and dense silica-alumina glass network inside the fly ash possess an insurmountable thermodynamic barrier, and conventional stirring cannot induce lattice distortion and defect evolution at the microscopic level. The severe reduction in the contact area at the reaction interface means that even if the same thermal excitation field is maintained subsequently, the mass transfer resistance still cuts off part of the pathway for the conversion of the inert phase to the active acid salt.

[0100] The data from Comparative Example 2 reflect the impact of the lack of mineralization media on phase transformation reconstruction. The silicon conversion rate of this sample dropped to 38.92%, and the corresponding final alumina recovery yield was only 10.12 kg. The thermal energy input in the mid-temperature range (850℃-980℃) could not provide the dissociation energy required to melt the strong Si-O-Si bond system. The system has a very high path dependence on the fluorine-containing fluxing liquid phase. When fluorine ions are missing, the solid-phase diffusion of active calcium oxide produced by the decomposition of carbide slag on the surface of ash particles is limited, which leads to the network replacement reaction being blocked at the interface.

[0101] The data from Comparative Example 3 show that the active silica-alumina conversion rate of its calcined clinker (86.88% and 90.75%) is close to that of Example 1, but the actual recovery output of silica and alumina is reduced to 11.23 kg and 12.87 kg, respectively. This discrepancy between the high efficiency of front-end activation and the extremely low output at the back end is due to the irreversible and severe chemical antagonism effect within the solution environment.

[0102] When clinker containing highly active dicalcium orthosilicate and dodecacalcium heptaaluminate is directly added to a strong alkaline medium at 95°C, the two phases dissolve simultaneously. The free silicate macromolecules and aluminate ions with steric hindrance meet within a very short time window and rapidly precipitate and associate with sodium ions in the liquid phase, spontaneously precipitating a hydrated sodium aluminosilicate sodalite phase with a three-dimensional network framework (commonly known as sodium silicate slag).

[0103] This associated reaction re-solidifies the dissociated silicon and aluminum elements within the irreversible slag matrix. The data comparison above verifies the necessity of the low-alkali, low-temperature, staged extraction process design. Utilizing the potential difference in dissolution rates between the calcium silicate and calcium aluminate phases under specific temperature fields and OH- concentration gradients, the liquid phase mass transfer channels are forcibly cut off before large-scale dehydration of aluminum occurs. This is the only engineering kinetic path to avoid system lock-up and collapse and ensure high yields of both silicon and aluminum products.

[0104] Test Example 4: Test objective: This test focuses on practical applications in water treatment engineering, aiming to evaluate the engineering performance of solid waste-derived filter media in terms of hydrodynamic permeability and chemical capture capacity of specific pollutants. The test subjects are the porous filter media based on alumina tailings prepared in Examples 1 to 5, and the comparative filter media prepared by sintering raw fly ash with conventional pore-forming agents in Comparative Example 4.

[0105] Test steps: Each batch of molded filter media was packed into a standard acrylic filter column with an inner diameter of 50 mm, and the packing height of the filter media layer was controlled to be 800 mm. A constant flow pump was started to introduce pure water downwards at a filtration rate of 10 m / h. After the flow stabilized, the dynamic filtration pressure drop at the top and bottom of the filter layer was read and recorded using a micro differential pressure gauge to evaluate the three-dimensional connectivity and head loss resistance of the filter media bed.

[0106] Accurately weigh each group of filter media powder after grinding and sieving, place them in an Erlenmeyer flask, and conduct a titration and oscillation adsorption experiment using a standard methylene blue solution. Record the number of milliliters of methylene blue solution consumed when the filter media reaches saturation adsorption, and calculate the methylene blue adsorption value per unit mass of filter media. This is used to macroscopically quantify the total pore volume and reaction surface area of ​​the material.

[0107] A copper sulfate solution with an initial concentration of 30 mg / L was prepared to simulate heavy metal wastewater. This wastewater was continuously pumped into a micro-penetration adsorption column packed with an equal amount of the test filter media at a flow rate of 5 bed volumes per hour (5 BV / h).

[0108] Effluent samples were collected periodically at the outlet of the penetration column, and the residual copper ion concentration in the solution was monitored using atomic absorption spectrometry. The breakthrough time when the effluent concentration reached 5% of the influent concentration (i.e., 1.5 mg / L) was recorded, and the dynamic saturated adsorption capacity of the filter media for copper ions was calculated by integrating the breakthrough curve.

[0109] Test data: Table 4. Test results of water treatment functional indicators of porous filter media in the examples and comparative examples.

[0110] in conclusion: Figure 4 This is a comparative test distribution chart of the water treatment functional indicators of the filter media of this invention; the chart contains two sub-charts arranged vertically, in which... Figure 4 (a) is a line spectrum showing the dynamic filtration pressure drop and methylene blue adsorption value distribution of each test bed. Figure 4 (b) is a line spectrum of the dynamic breakthrough time and saturated adsorption capacity of copper ions under heavy metal simulated wastewater test; the objects on the horizontal axis in the figure correspond to Examples 1 to 5 and Comparative Example 4 as the benchmark comparison.

[0111] According to the data in Table 4, the filter media prepared with different precursors showed differentiated test results in terms of macroscopic hydrodynamic behavior and interfacial adsorption capacity. The packed beds constructed in Examples 1-5 maintained a low resistance range of 12.8 kPa-17.5 kPa under constant flow velocity, while the methylene blue adsorption value all exceeded 34 mg / g. Considering the phase evolution patterns of the upstream refining process, this excellent hydrodynamic permeability is attributed to the in-situ foaming effect induced by the calcium carbonate at the bottom of the tailings in the high-temperature sintering section.

[0112] Compared to the limitation of externally added pore-forming agents being easily encapsulated by the liquid phase, the carbon dioxide gas spontaneously released by the tailings forms a connected three-dimensional pore network inside the green body. This gas phase expansion from the inside out not only gives the single particle filter material a huge internal surface area volume, but also reduces the risk of fluid short-circuiting and excessive clogging in the bed during engineering applications.

[0113] Test results show that this three-dimensional porous network enhances the adsorption and removal capacity of heavy metals. Figure 4 The dynamic penetration curve characteristics of (b) show that the penetration time of copper ions in the example group reached more than 168 min, and the saturated adsorption capacity was about 30 mg / g. The active calcium phase remaining at the bottom of the tailings during the aluminum leaching stage is the chemical basis for inducing this functional leap. These free calcium components are exposed to the fluid interface in large quantities after pore formation and spontaneously hydrate and recombine to form dense surface hydroxyl sites in the aqueous environment. This microstructure enables the filter media to overcome the limitation of simply relying on interception and provides a high-energy chemical coordination network for free divalent copper ions.

[0114] Compared with Comparative Example 4, which uses undisturbed fly ash, its bed pressure drop reached 48.7 kPa and its methylene blue adsorption value was only 9.2 mg / g, indicating that its structure is dense, has few interconnected pores and low surface activity. The undissociated crystalline phase and glass in the undisturbed fly ash undergo liquid phase shrinkage at high temperature, which restricts the formation of pores.

[0115] The closure of the structure and the reduction of surface adsorption sites resulted in a copper ion penetration time of 41 min and an adsorption capacity of 5.8 mg / g. The above test data verified the feasibility and advantages of using wet refining tailings to prepare environmentally friendly filter media. The intermediate extraction process removed the inert components that hindered pore formation and forcibly grafted carbon sources and active calcium sites onto the residue substrate, so that the material obtained by final sintering is not only a low-cost solid waste skeleton, but also evolved into a reactive filter medium with both excellent hydraulic flux and high chemical affinity.

Claims

1. A method for co-activating solid waste to extract aluminum and co-produce silica and porous filter media, characterized in that, Includes the following steps: Fly ash and carbide slag are mixed and calcium fluoride is added. The mixture is then ball-milled to obtain a mixed raw meal. The mixed raw materials are subjected to aerobic roasting, and after roasting at the highest constant temperature, they are cooled in the furnace to obtain activated clinker; After the activated clinker is crushed and sieved, it is added to an aqueous sodium hydroxide solution and stirred to leach. The solution is then filtered to obtain a sodium silicate enrichment solution and a primary filter cake. Carbon dioxide gas is introduced into the sodium silicate enrichment solution, and after aging, the solution is filtered, washed, and the precipitate is dried to obtain silica. The primary filter cake was added to a sodium carbonate aqueous solution and refluxed for leaching. Solid-liquid separation was performed to obtain sodium aluminate enriched mother liquor and aluminum-extracting tailings. Carbon dioxide gas was introduced into the mother liquor enriched with sodium aluminate to precipitate the precipitate, which was then filtered, washed, and calcined to obtain alumina powder. The aluminum extraction tailings are dried and ultra-finely ground to pass through a 200-mesh sieve. The dry tailings powder is then mixed with a composite pore-forming agent and a polymer binder. After being sprayed with atomized water, the powder is granulated. The raw material granules are preheated, sintered, kept warm, and cooled in the furnace to obtain porous water treatment filter media.

2. The method according to claim 1, characterized in that, When mixing fly ash and carbide slag, based on a total weight of 100 parts of fly ash and carbide slag, the amount of fly ash is 66.7 to 80 parts, and the amount of carbide slag is 20 to 33.3 parts; the amount of calcium fluoride added is 3 to 8 parts by weight. The conditions for the ultrafine ball milling are as follows: The ball-to-material ratio is controlled at (5-10):1, and the mixture is ultrafinely ball-milled at a speed of 300-500 rpm for 2-4 hours to achieve a characteristic particle size D50 of 5-15 μm for the mixed raw material.

3. The method according to claim 1, characterized in that, The parameters for the isothermal calcination are controlled as follows: The heating rate is 5-10℃ / min, the calcination constant temperature is set at 850-980℃, and the constant temperature holding time is 1.5-3h.

4. The method according to claim 1, characterized in that, The specific conditions for pulverizing and sieving the activated clinker are: pulverizing and passing it through a 100-mesh standard sieve; The sodium hydroxide aqueous solution has a mass fraction of 5-10%, and the liquid-to-solid ratio of the activated clinker to the sodium hydroxide aqueous solution is (4-8):1mL / g; Under a water bath at 60–90°C, mechanical stirring at a speed of 200–400 rpm is turned on, and the leaching time is controlled at 30–60 min. Carbon dioxide gas is introduced into the sodium silicate enrichment solution, and the pH value at the reaction endpoint is controlled at 7.5–8.

5. The solution is then left to stand and age at room temperature for 1–2 h.

5. The method according to claim 1, characterized in that, The specific conditions for reflux leaching in the sodium carbonate aqueous solution are as follows: The sodium carbonate aqueous solution has a mass fraction of 15-25%, and the liquid-solid ratio of the primary filter cake to the sodium carbonate aqueous solution is (3-6):1mL / g. Stir and reflux at 80–110°C for 1.5–3 hours; The calcination temperature after precipitation is controlled at 1000-1100℃, and the calcination time is 2h.

6. The method according to claim 1, characterized in that, The composite pore-forming agent is an inorganic-organic composite pore-forming agent, and the polymer binder is a cross-linked modified sodium alginate-polyacrylamide binder; When incorporating the inorganic-organic composite pore-forming agent and the cross-linked modified sodium alginate-polyacrylamide binder, based on 100 parts by weight of the dry powder of aluminum-removing tailings, the amount of the inorganic-organic composite pore-forming agent added is 2-5 parts by weight, the amount of the cross-linked modified sodium alginate-polyacrylamide binder added is 1-3 parts by weight, and the amount of atomized water sprayed is 10-20 parts by weight.

7. The method according to claim 6, characterized in that, The specific conditions for granulation and sintering are as follows: Spherical raw material pellets with a particle size of 3mm to 8mm are prepared by molding in a disc pelletizer at an inclination angle of 45° to 55° and a rotation speed of 15 to 30 rpm. The raw material particles are first preheated at 400-500℃ and kept at that temperature for 30-60 minutes, then heated to 1050-1180℃ for high-temperature microporous sintering and held at that temperature for 1-2 hours.

8. The method according to claim 6, characterized in that, The inorganic-organic composite pore-forming agent is made from raw material components comprising the following weight ratios: 100 parts ammonium bicarbonate, 100-200 parts corn starch; The preparation steps of the inorganic-organic composite pore-forming agent are as follows: The ammonium bicarbonate and corn starch were placed in a three-dimensional mixer and mechanically dry-mixed at room temperature and a speed of 30 r / min for 45 min. After being mixed evenly, the mixture was passed through a 100-mesh standard sieve, and the sieve-underfill material was collected to obtain the inorganic-organic composite pore-forming agent.

9. The method according to claim 6, characterized in that, The cross-linked modified sodium alginate-polyacrylamide environmentally friendly adhesive is made from raw materials containing the following components: 100 parts by weight of deionized water, 2-5 parts by weight of sodium alginate, 10-15 parts by weight of acrylamide, 0.1-0.3 parts by weight of potassium persulfate, and 0.05-0.15 parts by weight of N,N'-methylenebisacrylamide.

10. The method according to claim 9, characterized in that, The cross-linked modified sodium alginate-polyacrylamide environmentally friendly binder is prepared through the following specific steps: The sodium alginate is dissolved in the deionized water, and heated to 60-70°C in a water bath under nitrogen protection, with continuous mechanical stirring until completely dissolved; Then, the acrylamide, the potassium persulfate, and the N,N'-methylenebisacrylamide were added sequentially. The reaction was carried out under constant temperature of 60-70℃ with continuous mechanical stirring for 3-5 hours to form a viscous graft copolymer gel. After the reaction was completed, the product was washed with anhydrous ethanol to remove the precipitate. After being pulverized, it was dried in a vacuum drying oven at 60°C for 24 hours to obtain solid binder powder.